A Semi-Synthetic Diet and the Potential Important Chemicals for Mythimna separata (Lepidoptera: Noctuidae). Issue 6 (14th November 2019) - Jia, Jingwei; Sun, Shao-Lei; Kuang, Wenqing; Tang, Rui; Zhang, Zhan-Feng; Song, Chunman; Liu, Tong-Xian; Jing, Xiangfeng
Abstract: Armyworm feeding in large, destructive groups is hugely difficult to control and the oriental armyworm, Mythimna separata (Walk), is one such pest. In this study, we reported a semisynthetic artificial diet for the oriental armyworm. This diet is based on Ritter's diet, a formula developed for Heliothis zea . The survival of M. separata was extremely low and only around 2% insects can reach the adult stage on Ritter's diet. But, it can reach up to 100% if corn leaf powder (CLP) was mixed, and insects grew faster and gained more mass. After testing a set of mixtures of Ritter's diet and CLP, we found that 14.3% was the optimal proportion of CLP for making the artificial diet. We then used chloroform to extract CLP. Insect performance was still much better on Ch-extracted CLP diets than that on Ritter's diet, but it was poorer than that on the diets containing unprocessed CLP, suggesting that the essential factor(s) was only partially extracted from corn leaf. We then used methanol and dichloromethane, two solvents differing in their polarity, to process the extractions and analyzed the extracted chemicals using gas chromatography–mass spectrometry (GC-MS). Insects had a better performance on dichloromethane-extracted CLP diet in comparison to methanol-extracted one, indicating that the important factor(s) is more prone to methanol extraction. The reported recipe here is useful for the research on M. separata and possibly other grain-crop eating armyworms. The functions of the chemicals extracted from corn leaf tissue can be investigated in the future studies.